Miller's girl [videorecording (DVD)] - Bartlett, Jade Halley; Freeman, Martin, 1971-; Ortega, Jenna; Dominczyk, Dagmara, 1976-; Salahuddin, Bashir, 1976-; Adlon, Gideon, 1997- (Lionsgate, 2026)
A talented young writer embarks on a creative odyssey when her teacher assigns a project that entangles them both in an increasingly complex web. As lines blur and their lives intertwine, professor and protegee must confront their darkest selves while straining to preserve their individual sense of purpose and the things they hold most dear.